ANALISIS SISTEM PENGENDALIAN INTERNAL DAN KOMPETENSI SUMBER DAYA MANUSIA DALAM MENCEGAH ACCOUNTING FRAUD DENGAN AKUNTABILITAS KINERJA SEBAGAI VARIABEL INTERVENING - Yulianus Bramero Kurniawan Rugu; Muslichah Muslichah (ITB AAS INDONESIA, 2022)
This research is a causality study that aims to analyze the effect of the implementation of internal control systems and human resource competences on the prevention of accounting fraud with accountability performances as an intervening variable. The data in this study are primary data from 39 respondents who work at the Regional Finance Agency of East Manggarai Regency. The sampling technique in this study used the saturated sampling method using a survey method with questionnaire as a tool to collect data. Data analysis was carried out using the Partial Least Square method and hypothesis testing using the bootstrapping method using the SmartPLS 3. The results show that human resource competences has a significant effect on accountability performances and prevention of accounting fraud, accountability performances has a significant effect on prevention of accounting fraud. While the internal control system does not have a significant effect on accountability performances and prevention of accounting fraud. Accountability performances does not mediate the relationship between internal control systems and prevention of accounting fraud, while accountability performances mediates the relationship between human resource competences and prevention of accounting fraud.